Effect of silicon fertilization on wheat productivity and profitability in Southern Rajasthan - CHOUDHARY, ROSHAN; SHARMA, S K; CHOUDHARY, R S; YADAV, S K; JAT, GAJANAND; SINGH, HARI; SIDDARTHA NAIK, B SRI SAI (The Indian Journal of Agricultural Sciences, 2022)
Area under organic cultivation of wheat (Triticum aestivum L.) is increasing in India. The present two-year study was carried out during 2017–18 and 2018–19 to observe the yield performance of wheat with application of silicon solution (amorphous silica SiO2) under sub-humid conditions of southern plains and Aravalli Hills of Rajasthan. Factorial RBD with five levels of silicon concentration and three growth stages, viz. CRI, tillering and jointing stages were replicated thrice during rabi season of 2017–18 and 2018–19 at Udaipur, Rajasthan, India. Results revealed that application of silicon 8 g/litre water at tillering stage proved significantly superior in enhancing growth characteristics, yield attributes, yield and also gave maximum net returns of 110281/ha and B:C ratio of 2.32